Konseling Realitas untuk Mengatasi Siblings Rivalry Anak Usia Dini - Aprilia Dewi Suciati; Yanuari Srianturi (Ma'soem University, 2021)
This article aims to determine the sibling rivalry in early childhood in the concept of a reality counseling approach and the results of previous relevant research on sibling rivalry. Sibling rivalry is a form of competition between siblings, between brothers and sisters to win the attention and affection of parents. Every child has a unique personality and has different needs. This literature review discusses sibling rivalry behavior that occurs in early childhood in the concept of theory and reality counseling. WDEP is a stage of reality counseling where the counselor helps the counselee to describe what the counselee wants, the behavior that the counselee should do, evaluate himself, and plan what the counselee wants so that it can help reduce the behavior of siblings rivalry in early childhood. This research employed descriptive qualitative method using a literature review. The results of this research of literature indicate that the application of reality counseling can reduce sibling rivalry behavior in early childhood.